2020
DOI: 10.3389/fmolb.2020.00151
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Carrier Involvement in Mitochondrial Dysfunctioning in the Brain White Matter

Abstract: Glutamate homeostasis is an important determinant of health of the central nervous system (CNS). Mitochondria play crucial roles in glutamate metabolism, especially in processes with a high energy demand such as action potential generation. Mitochondrial glutamate carriers (GCs) and aspartate-GCs (AGCs) regulate the transport of glutamate from the cytoplasm across the mitochondrial membrane, which is needed to control energy demand, lipid metabolism, and metabolic activity including oxidative phosphorylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 107 publications
0
8
0
Order By: Relevance
“…Interestingly, five of these potentially interacting proteins of ADGRV1 were also found under the GO term "L-glutamate import" (subtitle Table S1; Figure S2C, D) suggesting a link to the glutamate homeostasis, a major function of astrocytes in the CNS. In particular, the two plasma membrane proteins, namely the excitatory amino acid transporters SLC1A1/EAAT3 and SLC1A3/EAAT1/GLAST1 are core proteins of the glutamate uptake machinery in astrocytes (Cuellar-Santoyo et al, 2023) and the three mitochondrial carrier family proteins, SLC25A12/Aralar, SLC25A13, and SLC25A22 are related to the glutamate metabolization in the TCA (Table S1, subtitle 3: Transporters and L-Glutamate import; Figure S2D) (Hillen and Heine, 2020). These findings indicated that ADGRV1 potentially interacts with numerous proteins that are important for the astrocyte functions in the nervous system.…”
Section: Affinity Proteomics Reveals the Interaction Of Adgrv1 With P...mentioning
confidence: 99%
“…Interestingly, five of these potentially interacting proteins of ADGRV1 were also found under the GO term "L-glutamate import" (subtitle Table S1; Figure S2C, D) suggesting a link to the glutamate homeostasis, a major function of astrocytes in the CNS. In particular, the two plasma membrane proteins, namely the excitatory amino acid transporters SLC1A1/EAAT3 and SLC1A3/EAAT1/GLAST1 are core proteins of the glutamate uptake machinery in astrocytes (Cuellar-Santoyo et al, 2023) and the three mitochondrial carrier family proteins, SLC25A12/Aralar, SLC25A13, and SLC25A22 are related to the glutamate metabolization in the TCA (Table S1, subtitle 3: Transporters and L-Glutamate import; Figure S2D) (Hillen and Heine, 2020). These findings indicated that ADGRV1 potentially interacts with numerous proteins that are important for the astrocyte functions in the nervous system.…”
Section: Affinity Proteomics Reveals the Interaction Of Adgrv1 With P...mentioning
confidence: 99%
“…Metabolic reprogramming is induced by glutamine and derived metabolites, which makes this metabolism of interest to target in mitochondria, including in cancer [50]. Finally, glutamate transport into and out mitochondria is increasingly investigated, as glutamate is a powerful neurotransmitter as GABA neurotransmitter (gamma aminobutyric acid) [51]. Mitochondrial glutamate carriers include GC1/SLC2A22 (glutamate carrier 1) and GC2/SLC25A18 for the glutamate transport over mitochondrial IM, and mitochondrial aspartate-glutamate carriers include AGC1/Aralar/SLC25A12 (aspartate-glutamate carrier 1), AGC2/SLC25A13/Citrin [51].…”
Section: Mitochondrial Metabolomementioning
confidence: 99%
“…Finally, glutamate transport into and out mitochondria is increasingly investigated, as glutamate is a powerful neurotransmitter as GABA neurotransmitter (gamma aminobutyric acid) [51]. Mitochondrial glutamate carriers include GC1/SLC2A22 (glutamate carrier 1) and GC2/SLC25A18 for the glutamate transport over mitochondrial IM, and mitochondrial aspartate-glutamate carriers include AGC1/Aralar/SLC25A12 (aspartate-glutamate carrier 1), AGC2/SLC25A13/Citrin [51]. Mitochondrial dysfunction, neuron activity disturbance, and myelin metabolism alteration are induced by GC and AGC dysregulation [51].…”
Section: Mitochondrial Metabolomementioning
confidence: 99%
See 1 more Smart Citation
“…Another equally viable explanation for concurrent GSH and glutamate deficit in schizophrenia focusses on the putative primacy of the glutamatergic deficit [ 138 ]. A reduction in glutamate transport in the mitochondria may disrupt mitochondrial function and cause an increase of free radical production [ 139 ] and the consequent adaptive increase in GSH consumption. Finally, a third factor such as altered resting-state cerebral blood flow may lead to mitochondrial dysfunction, leading to both an increase in free radical species followed by lowered GSH and concomitant glutamatergic deficit.…”
Section: Glutathione—glutamate Relationshipmentioning
confidence: 99%